How do you solve abs(x+3)=abs(7-x)?

1 Answer
Mar 30, 2015

One way(Method 1) would be to replace each of the absolute value expressions with 2 possible expressions (one positive and one negative). For the given example there are two absolute value expression and all 4 possible combinations would need to be considered.

An alternative (Method 2) would be to square both sides and solve.

Method 1
-(x+3) = -(7-x)
rarr -2x = -4
rarr x = 2

-(x+3) = +(7-x)
rarr -3 = 7 impossible; extraneous result; ignore

+(x+3) = -(7-x)
rarr 3=-7 Impossible; extraneous result; ignore

+(x+3) = +(7-x)
rarr 2x = 4
rarr x = 2 (a duplicate of the second result)

The only solution is x=2

Method 2
(abs(x+3))^2 = (abs(7-x))^2

cancel(x^2) +6x + 9 = 49 -14x +cancel(x^2)
rarr 20x = 40
x=2